Stroop performance in depressive patients: a preliminary report - Markela-Lerenc, Jaana; Kaiser, Stefan; Fiedler, Peter; Weisbrod, Matthias; Mundt, Christoph (Journal of affective disorders, 2006)
Background - The Stroop interference test requires executive control functions, in particular inhibition of a learned routine (in this case word reading). Depressive patients show deficits on tests of executive function. However, the impact of confounding variables like type of depression and anxiety level is not yet elucidated for depressive patients. This is of clinical importance, since executive functions seem to play an important role in predicting treatment response and functional outcome. - Methods - 23 depressive patients and 27 healthy subjects performed a computerized mixed trial Stroop task. Depressive patients were divided according to DSM-IV diagnosis into melancholic and non-melancholic subgroups. Furthermore the level of anxiety was assessed in all subjects. - Results - When depressed patients were analyzed as a whole group, they showed only a trend towards higher Stroop interference effect at the beginning of the task. When analysis was performed using according to DSM-IV defined melancholic and non-melancholic subgroups, only non-melancholic patients were impaired in the Stroop task compared to melancholic patients and healthy subjects. - Limitations - The sample size was small resulting in low statistical power. Furthermore, the patients were medicated. - Conclusions - The unexpected result that melancholic patients perform better than non-melancholic ones may be due to their more pronounced rigidity, which makes them more resistant against distraction. Hence, more detailed psychopathological assessment is desirable for future investigations in executive functions of melancholic patients.
Gesehen am 02.02.2021